Visual Meaning in Digital Protests: The Use of Brave Pink and Hero Green in Social Media after the August 28–30, 2025 Demonstration - Maskuri, M. Ibnu Naufal (SEMIOTIKA: Jurnal Komunikasi, 2025)
This study discusses the visual meaning of digital protests after the August 28–30, 2025 demonstration in Indonesia, focusing on the use of Brave Pink and Hero Green colors on social media. This phenomenon shows how color functions as a medium of symbolic communication that shapes digital solidarity and collective consciousness of society. Through a qualitative approach with a visual content analysis method, this study examines how the two colors are articulated in public uploads and how their meanings are constructed and reproduced participatically in the digital space. The results showed that Brave Pink represents courage born of empathy and tenderness, while Hero Green represents hope, balance, and social vitality. The combination of the two gives birth to a visual discourse that marks a shift from confrontational protest to reflective and inclusive expression. This research confirms that color can function as a moral language that strengthens social connectedness in the digital world. Thus, the visual meaning in digital protests not only reflects the political attitudes of the community, but also shows the transformation of communication culture in the new media era.